(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today in the world, global competition is the basic element to define firms’ strategies as a result industrial economy has been experienced to pass toward to knowledge economy. At an age where total quality is of primary importance, efficiency can only be achieved by the successful utilization of human resources. Human resource management is one of the necessary needs of today’s business. Human resource management department has a very important role for supply of the human being to main resources of companies. Human resource management department has fundamental role for personnel recruiting, orientation and performance appraisal and so on. Human resource management issues to be addressed at the highest level in the organization and management of strategic decisions are required. This research will inform human resource management, scope and affecting factors on human resource management, human resource management functions and relationship between organizational effectiveness and human resources management.